On the Construction of Spherical Designs - Leal Junior, L.C.; Menegatto, V.A. (Trends in Computational and Applied Mathematics, 2007)
We study special subsets of the unit sphere in Rm, m 2, the socalled spherical designs in the literature. Among other things we introduce a new equivalence for the concept and investigate the construction of designs through rotations of Rm and projections over the equator of the sphere.